1998
DOI: 10.1007/s001250050937
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis on glycated collagen lattices

Abstract: There is growing evidence that the increased nonenzymatic glycation of various tissues, and the accumulation of advanced glycation endproducts (AGEs), are involved in the complications of diabetes mellitus. Nonenzymatic glycation occurs very slowly in longlived proteins within the extracellular matrix, including basement membrane proteins and tissue collagen. In fact, AGE accumulation in the basement membranes and collagen has been demonstrated in diabetic patients with a significant correlation with the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 30 publications
(36 reference statements)
1
47
0
1
Order By: Relevance
“…36 The differentiation of the HUVEC to form capillaries in vitro is dependent on many factors. These include vascular growth factors (VEGF, angiopoietin-1, angiopoietin-2), 37 integrins, 38 extracellular matrix, 39 and insulin. 40 Since the conditioned medium from the high glucose treated mesangial cells contained an altered mixture of vascular factors, the medium was also tested for its ability to inhibit in vitro capillary formation by the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…36 The differentiation of the HUVEC to form capillaries in vitro is dependent on many factors. These include vascular growth factors (VEGF, angiopoietin-1, angiopoietin-2), 37 integrins, 38 extracellular matrix, 39 and insulin. 40 Since the conditioned medium from the high glucose treated mesangial cells contained an altered mixture of vascular factors, the medium was also tested for its ability to inhibit in vitro capillary formation by the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated a diminished vascular tube formation in response to growth factors in a glycated collagen matrix. 8 In a hindlimb ischemia model, Tamarat et al demonstrated reduced endogenous angiogenesis in diabetic mice which was reversed by the administration of aminoguanidine, an inhibitor of AGE formation. 9 Second, diabetes is associated with alterations in proangiogenic growth factor signaling.…”
Section: Controlmentioning
confidence: 99%
“…4 -7 Second, exposure to chronic hyperglycemia leads to the nonenzymatic glycation of proteins and in particular, glycation of the extracellular matrix has been shown to impair the formation of new blood vessels. 8,9 Lastly, the presence of diabetes is associated with abnormalities in growth factor signaling which have not been well characterized, particularly in the myocardium. 10,11 An important limitation to the study of myocardial angiogenesis in the setting of diabetes is the lack of a validated large animal model that captures the functional, microcirculatory, and molecular abnormalities associated with diabetes, and is suitable for the induction of chronic myocardial ischemia.…”
mentioning
confidence: 99%
“…The angiogenic role of AGEs in vitro remains somewhat controversial: antiangiogenic (16) or proangiogenic (17). Some reports showed the involvement of AGEs in impaired angiogenic response in diabetic animals in vivo; inhibition of AGE formation in diabetic mice is shown to restore ischemia-induced angiogenesis in peripheral limbs (18), and AGEs inhibition with soluble RAGE can restore angiogenic potential during wound healing in diabetic mice (19).…”
mentioning
confidence: 99%